You learn as they earn. - Daniel, Caroline (New Statesman, 1998)
Discusses the move of the British government under Prime Minister Tony Blair to implement the vision of creating an information technology literate workforce for the 21st century. Various programs and projects being designed and implemented in Britain to achieve the vision; Preliminary results of the programs; Estimated cost in implementing the projects.